Biosecurity in the global age : biological weapons, public health, and the rule of law - Fidler, David P.; Gostin, Larry O. (Larry Ogalthorpe) (Stanford, Calif. : Stanford Law and Politics, 2008)
"Biosecurity in the GlobalAge offers a comprehensive analysis of the dramatic transformations reshaping how the international community addresses biological weapons and infectious diseases. Fidler and Gostin argue that the arms control approach first outlined in the Biological Weapons Convention no longer dominates, and they identify four emerging policy trends - the criminalization of biological weapons, the regulation of the biological sciences, the management of the biodefense imperative,and the preparation for biological weapons attack. The authors look at the links between security and public health policy, both at the national and international level, and scrutinize the difficulty of developing policies that improve defenses against both biological weapons and the threat of infectious diseases from new viral strains."
"The renewed threat of biological weapons highlights the importance of crafting policy responses informed by the rule of law. This book explores patterns in recent governance initiatives and advocates building a "global biosecurity concert" as a way to address the threats presented by biological weapons and infectious diseases in the early 21st century."--BOOK JACKET.
1. Introduction: The Challenge of Biosecurity in the Twenty-First Century -- Pt. I. Biosecurity and Biological Weapons -- 2. The Problem of Biological Weapons -- 3. The New World of Biological Weapons Governance -- Pt. II. Biosecurity and Public Health -- 4. The Securitization of Public Health -- 5. The New World of Public Health Governance -- Pt. III. Biosecurity, the Rule of Law, and Globalized Governance -- 6. Biosecurity and the Rule of Law -- 7. Globalizing Governance: Toward a Global Biosecurity Concert -- 8. Conclusion: The Burden and Opportunity of Biosecurity in the Global Age -- Annex 1. U.S. Government Select Agent List -- Annex 2. Geneva Protocol of 1925 -- Annex 3. Biological Weapons Convention of 1972 -- Annex 4. Provisions Connected to Human Rights in the International Health Regulations (2005)
Includes bibliographical references and index.
Keywords: Biological warfare -- Prevention; Biological weapons -- Law and legislation; Bioterrorism -- Prevention; Public health laws